2018
DOI: 10.1186/s13287-018-0806-4
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular joint regeneration: proposal of a novel treatment for condylar resorption after orthognathic surgery using transplantation of autologous nasal septum chondrocytes, and the first human case report

Abstract: BackgroundUpon orthognathic mandibular advancement surgery the adjacent soft tissues can displace the distal bone segment and increase the load on the temporomandibular joint causing loss of its integrity. Remodeling of the condyle and temporal fossa with destruction of condylar cartilage and subchondral bone leads to postsurgical condylar resorption, with arthralgia and functional limitations. Patients with severe lesions are refractory to conservative treatments, leading to more invasive therapies that range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 44 publications
0
16
0
1
Order By: Relevance
“…Furthermore, these results were consistent with results previously reported for early TMJOA generated by surgical manipulation of the joint 30,31 , local application of chemicals 32,33 , and genetic modification 34,35 . Unlike rheumatoid arthritis and synovitis, TMJOA has a primarily noninflammatory origin 36,37 . The pathological process in TMJOA is characterized by deterioration and abrasion of the articular cartilage and local thickening and remodeling of the underlying bone 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these results were consistent with results previously reported for early TMJOA generated by surgical manipulation of the joint 30,31 , local application of chemicals 32,33 , and genetic modification 34,35 . Unlike rheumatoid arthritis and synovitis, TMJOA has a primarily noninflammatory origin 36,37 . The pathological process in TMJOA is characterized by deterioration and abrasion of the articular cartilage and local thickening and remodeling of the underlying bone 36 .…”
Section: Discussionmentioning
confidence: 99%
“…The maximum mouth opening variable that was examined in all qualifying reports [ 55 , 56 , 57 , 75 , 76 ]. Due to a weaker level of evidence (single case), the study by de Souza Tesch et al was not taken into account in this synthesis [ 76 ]. The range of mandibular mobility increased during post-intervention observation.…”
Section: Resultsmentioning
confidence: 99%
“…All of the studies that were identified in the course of this systematic review showed a reduction of pain and an increase of the MMO due to the intra-articular injections of stem cells [ 55 , 56 , 57 , 75 , 76 ]. The pain level was measured with the VAS scale in three studies [ 55 , 57 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Respecto al manejo, se han sugerido múltiples alternativas 8 : conservadoras como la férula oclusal, o tratamientos que incluyen la cirugía ortognática, a pesar de existir riesgo de recaída 9,10 .…”
Section: Discussionunclassified